The structure of training loads in the preliminary specialization of sprint running in Russia and China - Stanula, A.; Szmatlan-Gabrys, U.; Wou-Yng (2001)
The purpose of this study was to make comparable analysis of training loads undertaken by female sprinters at 12-13 years of age in Russia and china. On the basis of the analysis of the obtained results an attempt was made to determine sports instruction at the preliminary stage of specialization, as well as determine the most characteristic features predominant in Russia and China. In order to determine the organization of a year`s training cycle, 75 training plans from Moscow, Sain Petersburg, Vowgograd and Shanghai were analyzed. Theoretical assumptions of training processes, based an analysis of practical solutions mean it is possible for coaches to determine a predominant direction of work with an athlete at the specific stage of his or her sports development, as well as to register the changes occurred during sports activities. Analysis of the research material enabled the authors to work out the characteristic training process of these young female sprinters, such as: training aims, training, methods, training media and maximal training workload. Table 1. Specification of training media and workloads applied within a one year period in 12-13 year old female sprinters at the stage of preliminary specialization. Training means with the following values x ± Sx Russia n=45 x ± Sx China n=30 Difference Student`s "t" test